Design method of immiscible dissimilar welding (Mg/Fe) based on CALPHAD and thermodynamic modelling - Zang, Chengwei; Zhao, Xiaoye; Xia, Hongbo; Wen, Wei; Tan, Zhuoming; Tan, Caiwang; Rivera-Díaz-del-Castillo, Pedro E.J. (Materials & design, 2024)
Joining dissimilar metals is a major challenge in joining technology; the weldability of immiscible systems is especially challenging. In this study, a design methodology for dissimilar welding is suggested. The Miedema model and Toop model are developed to calculate the thermodynamics of quaternary alloy systems (Mg-Fe-Al-Cu). Finite element modelling (FEM) of temperature fields and the calculation of phase diagrams (CALPHAD) are combined to provide prerequisite information for modelling. As a test subject, laser welded lap configuration joints of AZ31B magnesium alloy and DP590 steel with a copper coating were put into the design scheme. The interfacial elemental diffusion and formation of intermetallics (IMCs) along the interface during the welding process are predicted. This simulation design scheme predicts the interfacial reaction kinetics and identifies whether the intermediate element works or not. The effects of the Cu coating thickness on the weld constitution, interfacial microstructures and mechanical properties were studied. Cu coating promotes the weld formation fostering the metallurgical reaction of the fusion zone (FZ) with the steel brazing interface. The mechanism of interfacial reactions during the welding-brazing process has been clarified. The Vickers hardness distribution across the interface shows that the Cu-IMCs are ductile. •Design method based on thermodynamics was proposed to select an interlayer for joining immiscible metals, e.g. Fe/Mg.•Cooper coating was found to promote the interfacial reaction and contribute to improve joint strength.•The effects of the Cu coating thickness on the interfacial microstructures and mechanical properties were studied.•The mechanism of interfacial reactions during the welding-brazing process has been clarified.